Pseudotumor cerebri presenting by neck rigidity and torticollis: A case report: Pseudotumor cerebri by neck rigidity and torticollis - aminzadeh, vahid; Hassanzadeh Rad, Afagh (Iranian Journal of Child Neurology, 2023)
Pseudotumor cerebri syndrome is an uncommon disease in children. It’s on time diagnosis and treatment can prevent irreversible visual loss. Although headache is the most common complaint of children with this syndrome, in this case report, the authors reported a child with neck rigidity and torticollis which declined by the reduction of intracranial pressure. Despite the importance of torticollis and neck rigidity which could be presented in various significant neurological disorders in need of thorough investigations, in the case of unexplained symptoms of those disorders, it is recommended to consider fundoscopic examinations for Pseudotumor cerebri syndrome to prevent its important complications.